PHYLOGENY OF IMMUNOGLOBULIN STRUCTURE AND FUNCTION : III. IMMUNOGLOBULINS OF THE CHICKEN - Leslie, Gerrie A. (The Rockefeller University Press, 1969)
Chicken 7.1S immunoglobulin was purified from whole chicken serum by DEAE-cellulose chromatography and Sephadex G-200 gel filtration. The macroglobulin was purified by a combination of salt precipitation and Sephadex G-200 gel filtration. Both immunoglobulin molecules yielded 75% heavy (H) chains and 25% light (L) chains when subjected to extensive reduction and alkylation followed by gel filtration in 5 M guanidine-HCl. Antigenically reactive H and L chains were obtained by partial reduction and alkylation followed by gel filtration in 5 M guanidine-HCl. The 7.1S and 16.7S immunoglobulin H chains were antigenically unrelated to each other, whereas the L chains were antigenically indistinguishable from one another. The 16.7S H chains were found to have a mass of ∼70,000, and the 7.1S H chains had a mass of 67,500. The mass of the L chains was ∼22,000. Sedimentation equilibrium studies of the 7.1S immunoglobulin molecule gave a mol wt of ∼170,000 which is in good agreement with the 179,000 predicted on the basis of 2 H and 2 L polypeptide chains. The 16.7S molecule was shown to have a mol wt of ∼890,000. A reductive subunit that has a mol wt of ∼174,000 has been isolated from the 16.7S molecule. These values are consistent with the chicken macroglobulin having five subunits, each of which has 2 H and 2 L chains. The hexose contents of the chicken 7.1S and 16.7S immunoglobulins are 2.2% and 2.6%, respectively. The extinction coefficients of the 7.1S and 16.7S immunoglobulins were 13.18 ± 0.04 and 12.72 ± 0.77, respectively, when measured in 0.3 M KCl. Based upon physical-chemical and antigenic characteristics, the 16.7S immunoglobulin most closely resembles IgM of mammals. The 7.1S immunoglobulin definitely belongs to a different class than the 16,7S immunoglobulin, but it does not align itself very well with any of the mammalian immunoglobulins. We propose that this molecule be designated as IgY. Furthermore, this designation would be useful for the immunoglobulins of other species for which there is insufficient correlation with any of the known human immunoglobulins.